AKHLAK DAN ADAB GURU PENDIDIKAN AGAMA ISLAM DALAM PERSPEKTIF KH. M. HASYIM ASY’ARI - Muhammad Abror Rosyidin (Journal of Research and Thought on Islamic Education (JRTIE), 2021)
Abstract: Islamic Religious Education is the most important part of the education system in Indonesia. This is because Islamic Religious Education is education, which contains moral, intellectual, and spiritual education. Meanwhile, teachers are the main component in the continuity of Islamic Religious Education (PAI). The number of PAI teachers continues to increase along with the number of schools and scholars of Islamic Education. However, the issue of the quality of basic competencies is the main problem. In the book Adab al ‘Alim wa al Muta'llim by Hadratussyaikh Hasyim Asy'ari explained that after faith and takwah, morals and ethic are very important foundations in the educational process. The purpose of this study is to determine the moral and ethic competence of teachers according to Hadratussyaikh Hasyim Asy'ari seen from the point of view of Islamic Education Philosophy. This study employed a qualitative approach to literature study with descriptive analytical data analysis. From this research, an ideal concept of basic competence can be generated according to KH. M. Hasyim Asy'ari Thought, which consists of 9 points. All of these points are in accordance with the Law of the Republic of Indonesia number 14 of 2005 concerning Teachers Chapter IV Articles 1, 2, and 10 which confirms that teacher competence includes pedagogic competence, personality competence, social competence, and professional competence obtained through professional education. In addition, it is also in accordance with the basic competencies of teachers, namely personal competence and social competence. These basic competencies can also be applied in all Islamic-based educational institutions to improve the quality of morals, ethics and adab of education personnel, especially for teachers. Keywords: Moral Competence, Hasyim Asy'ari, Teacher, Islamic Education, Islamic Education Philosophy.